Comparing quantitative image parameters between animal and clinical CT-scanners: a translational phantom study analysis - Vellala, Abhinay; Mogler, Carolin; Haag, Florian; Tollens, Fabian; Rudolf, Henning; Pietsch, Friedrich; Wängler, Carmen; Wängler, Björn; Schoenberg, Stefan O.; Froelich, Matthias F.; Hertel, Alexander (Frontiers in Medicine, 2024)
This study compares phantom-based variability of extracted radiomics features from scans on a photon counting CT (PCCT) and an experimental animal PET/CT-scanner (Albira II) to investigate the potential of radiomics for translation from animal models to human scans. While oncological basic research in animal PET/CT has allowed an intrinsic comparison between PET and CT, but no 1:1 translation to a human CT scanner due to resolution and noise limitations, Radiomics as a statistical and thus scale-independent method can potentially close the critical gap.Two phantoms were scanned on a PCCT and animal PET/CT-scanner with different scan parameters and then the radiomics parameters were extracted. A Principal Component Analysis (PCA) was conducted. To overcome the limitation of a small dataset, a data augmentation technique was applied. A Ridge Classifier was trained and a Feature Importance-and Cluster analysis was performed.performance with 93% accuracy, but faced challenges in generalization with a test accuracy of 62%.These results show that radiomics has great potential as a translational tool between animal models and human routine diagnostics, especially using the novel photon counting technique. This is another crucial step towards integration of radiomics analysis into clinical practice.